EuroSurg: Across Europe a new novel student-driven research group in surgery - Özkan, Bahar Büşra; Özbalcı, Gökhan Selçuk; Tavuz, Aziz İhsan; Demirci, Zeynep Şifa; Baki, Bahadır Emre; Tatar, Ozan Can (My University, 2016)
In 2013, a student-oriented working group called STARSurg (The Student Audit and Research in Surgery)directed to medical students and surgical residents was founded in the UK. STARSurg is a group offeringstudents the opportunity to participate in high-quality studies and encouraging them to be cliniciansengaged in active research in the future (1). The first study of STARSurg was joined by more than 250students from 109 hospitals. This study was related to the post-operative impacts of nonsteroidal antiinflammatory drugs in patients undergoing major gastrointestinal tract surgery, and was performedprospectively on 1500 patients. All participants were co-authors in the publication on completion of thestudy (2). STARSurg have been established in all schools in England and Ireland, and now includes morethan 180 hospitals. All manuscripts of STARSurg projects can be accessed through PubMed and can beused as references. Everyone involved in studies is included in these publications.

İngiltere’de; 2013 yılında tıp öğrencileri ve cerrahi asistanlarından oluşan STARSurg (The Student Audit and Research in Surgery) adı altında öğrenci odaklı bir çalışma grubu kuruldu. STARSurg, öğrencilere yüksek kaliteli çalışmalara katılma fırsatı sunan ve gelecekte aktif araştırmalar yapan klinisyenler olmaları için onları teşvik eden bir gruptur (1). STARSurg’ün ilk çalışmasına 109 hastaneden 250’den fazla öğrenci katıldı. Bu çalışma majör gastrointestinal sistem cerrahisi yapılan hastalarda non-steroid anti-inflamatu var ilaçların postoperatif etkileriyle ilgiliydi ve 1500 hastanın üzerinde prospektif olarak gerçekleştirildi. Tüm katılımcılar, çalışma sonundaki yayında ortak yazar oldular.
EuroSurg: Cerrahide, öğrenci odaklı Avrupa çapında yürütülen alışılmışın dışında yeni bir çalışma grubu
Keywords: Surgical; General Surgery; Cerrahi; Genel Cerrahi